1969
DOI: 10.1136/thx.24.6.722
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary monosporosis: An uncommon pulmonary mycotic infection

Abstract: At that time he gave a history of pleuritic type chest pain, cough, and blood-streaked sputum. Physical examination revealed bilateral crepitations in the lungs, and his chest radiograph showed dense fibrotic infiltration over the entire right lung field with evidence of cavitation in the right upper lobe. On the left there were scattered, less dense infiltrations in the lower two-thfirds. Sputum smears for acid-fast bacilli initially were reported as Gaffky VI. Subsequent sputa were negative. No cultures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In reviews by Lutwick et al, Reddy et al, and Jung et al, the authors identified preformed cavities in 13 out of 14 cases (211,260,352). Filaments of mycelium (plectenchyma) and conidia were found in large residual cavities in a resolved case of tuberculosis (10).…”
Section: Epidemiology Of Human Infectionsmentioning
confidence: 99%
“…In reviews by Lutwick et al, Reddy et al, and Jung et al, the authors identified preformed cavities in 13 out of 14 cases (211,260,352). Filaments of mycelium (plectenchyma) and conidia were found in large residual cavities in a resolved case of tuberculosis (10).…”
Section: Epidemiology Of Human Infectionsmentioning
confidence: 99%
“…Of the three patients reported by Reddy et al . [230], one was skin tested with an extract of S. apiospermum , but gave no response. Rippon and Carmichael [216] reported a case of transient endobronchial colonization.…”
Section: Characteristics Of Diseasementioning
confidence: 99%
“…These fungi have been recognized as etiologic agents of a variety of clinically apparent infections including pulmonary mycoses (25), meningomycoses (5), keratomycoses (4), and infection of the prostate gland (19). Infections of domestic animals also have been reported (13).…”
Section: Petriellidium (Allescheria) Boydii and Its Imperfect Formmentioning
confidence: 99%